A prospective study of diagnostic accuracy of multidisciplinary team and radiology reporting of preoperative colorectal cancer local staging. Issue 1 (17th June 2022) - Bedrikovetski, Sergei; Dudi‐Venkata, Nagendra N.; Kroon, Hidde M.; Traeger, Luke H.; Seow, Warren; Vather, Ryash; Wilks, Michael; Moore, James W.; Sammour, Tarik
Abstract: Introduction: The aim of this study was to correlate and assess diagnostic accuracy of preoperative staging at multidisciplinary team meeting (MDT) against the original radiology reports and pathological staging in colorectal cancer patients. Methods: A prospective observational study was conducted at two institutions. Patients with histologically proven colorectal cancer and available preoperative imaging were included. Preoperative tumor and nodal staging (cT and cN) as determined by the MDT and the radiology report (computed tomography [CT] and/or magnetic resonance imaging [MRI]) were recorded. Kappa statistics were used to assess agreement between MDT and the radiology report for cN staging in colon cancer, cT and cN in rectal cancer, and tumor regression grade (TRG) in patients with rectal cancer who received neoadjuvant therapy. Pathological report after surgery served as the reference standard for local staging, and AUROC curves were constructed to compare diagnostic accuracy of the MDT and radiology report. Results: A total of 481 patients were included. Agreement between MDT and radiology report for cN stage was good in colon cancer ( k = .756, Confidence Interval (CI) 95% .686–.826). Agreement for cT and cN and in rectal cancer was very good (kw = .825, CI 95% .758–.892) and good (kw = .792, CI 95% .709–.875), respectively. In the rectal cancer group that received neoadjuvant therapy, agreement on TRG was very good (kw = .919, CI 95% .846–.993). AUROC curves using pathological staging indicated no difference in diagnostic accuracy between MDT and radiology reports for either colon or rectal cancer. Conclusion: Preoperative colorectal cancer local staging was consistent between specialist MDT review and original radiology reports, with no significant differences in diagnostic accuracy identified. Abstract : Graphical Abstract : Colorectal cancer local staging using preoperative imaging may differ between the multidisciplinary team (MDT) opinion and original radiology report. This is the first prospective study to compare diagnostic agreement between a specialised colorectal cancer MDT and the radiology report in this setting, demonstrating consistent local staging between the two modalities.